2019
DOI: 10.21272/jes.2019.6(1).e1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Concave-Cut Baffles Effect in Shell-and-Tube Heat Exchanger

Abstract: In this paper, the performance of shell-and-tube heat exchangers with single-segmental baffle and varying configurations of concave-cut baffles (10, 15 and 20 %) was investigated. The study was carried out for a heat exchanger having either engine oil, water and air as shell-side fluid. For each configuration of the baffles, the results of both the the k-ε and RNG k-ε turbulent models were in very close agreement. The heat exchangers with concavecut baffles had higher pressure drops and lower performance facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…New methods of separating multicomponent systems have been created for example separation in a vortex flow [13], separation under the action of a magnetic field [14], inertia-filtrating, gas dynamic, vibration-inertial, and acoustic separation. The ways for intensification of the operating process [15,16], and methodology of numerical simulations of heat and mass exchange processes, as well as approaches to improve parameters for the corresponding multi-functional oil-gas separators and shell-and-tube heat exchangers, are presented in [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…New methods of separating multicomponent systems have been created for example separation in a vortex flow [13], separation under the action of a magnetic field [14], inertia-filtrating, gas dynamic, vibration-inertial, and acoustic separation. The ways for intensification of the operating process [15,16], and methodology of numerical simulations of heat and mass exchange processes, as well as approaches to improve parameters for the corresponding multi-functional oil-gas separators and shell-and-tube heat exchangers, are presented in [17,18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lalot et al (1999) showed experimentally that a perforated plate with holes of equal diameter in the inlet header increased the heat transfer efficiency [10]. Recently, numerical studies have been conducted to increase the thermal performance of heat exchangers and air distribution devices by considering a perforated plate [11], baffles [12], or varying the transverse and longitudinal pitches of tube bundles [13].…”
Section: Introductionmentioning
confidence: 99%
“…They obtained the mathematical model for determining the dependence of the average velocity on the flow rate, perforated plate area, and diameter of holes. Petinrin et al [12] numerically investigated the performance of shell-and-tube heat exchangers with single segmental baffles and varying configurations of concave-cut baffles. Their numerical results generally showed that shell-and-tube heat exchangers with concave-cut baffles had a lower performance as compared with the single-segmental baffle type.…”
Section: Introductionmentioning
confidence: 99%